Scoping review to identify and map the health personnel considered skilled birth attendants in low-and-middle income countries from 2000-2015. - Amy J Hobbs; Ann-Beth Moller; Alisa Kachikis; Liliana Carvajal-Aguirre; Lale Say; Doris Chou (PLoS ONE, 2019)
Introduction The "percentage of births attended by a skilled birth attendant" (SBA) is an indicator that has been adopted by several global monitoring frameworks, including the Sustainable Development Goal (SDG) agenda for regular monitoring as part of target 3.1 for reducing maternal mortality by 2030. However, accurate and consistent measurement is challenged by contextual differences between and within countries on the definition of SBA, including the education, training, competencies, and functions they are qualified to perform. This scoping review identifies and maps the health personnel considered SBA in low-to-middle-income-countries (LMIC). Methods and analysis A search was conducted inclusive to the years 2000 to 2015 in PubMed/MEDLINE, EMBASE, CINAHL Complete, Cochrane Database of Systematic Reviews, POPLINE and the World Health Organization Global Index Medicus. Original primary source research conducted in LMIC that evaluated the skilled health personnel providing interventions during labour and childbirth were considered for inclusion. All studies reported disaggregated data of SBA cadres and were disaggregated by country. Results The search of electronic databases identified a total of 23,743 articles. Overall, 70 articles were included in the narrative synthesis. A total of 102 unique cadres names were identified from 36 LMIC countries. Of the cadres included, 16% represented doctors, 16% were nurses, and 15% were midwives. We found substantial heterogeneity between and within countries on the reported definition of SBA and the education, training, skills and competencies that they were able to perform. Conclusion The uncertainty and diversity of reported qualifications and competency of SBA within and between countries requires attention in order to better ascertain strategic priorities for future health system planning, including training and education. These results can inform recommendations around improved coverage measurement and monitoring of SBA moving forward, allowing for more accurate, consistent, and timely data able to guide decisions and action around planning and implementation of maternal and newborn health programmes.